THE EFFECT OF PROFITABILITY, LEVERAGE AND COMPAY SIZE ON COMPANY VALUE IN THE BANKING SECTOR THAT GO PUBLIC IN INDONESIA STOCK EXCHANGE (IDX) PERIOD 2020-2022 - Hardianti; Muryani Arsal; Muchriana Muchran (Jurnal Media Akademik (JMA), 2024)
The study aims to examine the effect of Profitability, Leverage and Company Size on Company Value in the Banking Sector that Go Public in Indonesia Stock Exchange (IDX) period 2020- 2022. This study uses a quantitative method that aims to see the relationship between variables. The data collection technique used is documentation. The population in the financial statements of the Banking Sector that Go Public in Indonesia Stock Exchange (IDX). And the sample is financial statements of the Banking Sector that Go Public in Indonesia Stock Exchange (IDX) for 3 (three) years calculated quarterly. The result of the research had tested classical assumption such as normality assumption, multicollinearity, and heteroscedasticity.by applying multiple linear regression techniques in the process of data analysis. The result showed that partially profitability (ROA), Leverage (DER) didn’t influence on the Company value and Size Company influence on the Company Value.